A case of pulmonary lymphoproliferative disorder presenting rapidly progressive respiratory failure. Issue 5 (2nd April 2019) - Fujita, Kohei; Ishigami, Kenjiro; Tanaka, Hiroyuki; Moriyoshi, Koki; Mio, Tadashi
Abstract : A 72‐year‐old woman presented with acute onset of shortness of breath and fatigue over several days, and was found to be in acute respiratory failure. Computed tomography of the chest revealed diffuse ground‐glass opacities, crazy‐paving, multiple nodules, and a large mass in the right lower lobe. She was diagnosed with B‐cell lymphoma and a pulmonary lymphoproliferative disorder (PLD). PLD is known to present with a variety of radiographic patterns. The course of PLD is usually one of slow progression, and acute respiratory failure is a rare presentation. Physicians should be aware that acute respiratory failure can be caused by PLD. Abstract : A 72‐year‐old woman presented with acute onset of shortness of breath and fatigue over several days, and was found to be in acute respiratory failure. Computed tomography of the chest revealed massive ground‐glass opacity and partial crazy‐paving appearance with multiple nodules across all the lobes of the lung and a large mass in the right lower lobe. She was diagnosed with B‐cell lymphoma and the abnormal lung shadow was considered to be a result of a pulmonary lymphoproliferative disorder (PLD). PLD is known to present with various radiographic patterns. However, the progression of PLD is usually slow, and acute respiratory failure is very rare. Physicians should be aware that acute respiratory failure can be caused by PLD.